XXIII Certamen Nacional de Ceramica 1998 : Caja Madrid. - Marín-Medina, José (Madrid : Obra social Caja Madrid, 1998)
de Alba, Beatriz ; Senoo, Naoki ; Pérez Llorente, Susana ; González González Luis ; Canencia Sánchez, Elena ; Fuentes Señor, Abigail ; Puerto Losana, Carmen ; Pérez, Juan ; Gascón Blanco, Patricia ; de Gaula, Lila ; Xifra Olivé, Lluis ; Fernández Dévora, María Jesús ; Pañella i Demunt, Josep ; Adame Alonso, José Manuel ; de Mar Agudo Reig, María ; Gálvez Marrón, Francisco ; Rubio Carrasco, Luis Miguel ; Montalvo Morales, Mercedes ; Manero de la Cruz, Alicia ; González, Gloria ; Torres Burguillos, Miguel ; González Tostado, Belén ; Pedraza Díaz, Beatriz ; García Cossío, Mónica ; Paulo, Cuca ; Folch Schulz, Catalina ; González Navarro, Ana María ; Niño Ray, Belén ; Birabén, Mabi ; González Sanjuán, Susana ; Monfort, Reyes ; Cofán, Lina
Schenking Flanders DC
boek